Laparoscopic versus Robotic gastric cancer surgery: Short-term Outcomes. Systematic Review and Meta-analysis of 25 521 patients - Pedro Felgueiras Loureiro (2023)
Background: Gastric cancer has the third highest cancer-related mortality worldwide. There is no consensus regarding the optimal surgical technique to perform curative resection surgery. Objective: Compare laparoscopic and robotic gastrectomy regarding short-term outcomes in patients with gastric cancer. Materials and Methods: This systematic review was conducted according to the PRISMA guidelines. We searched the following topics: "Gastrectomy", "Laparoscopic" and "Robotic Surgical Procedures". The included studies compared short-term outcomes between laparoscopic and robotic gastrectomy. Individual risk of bias was assessed with the MINORS scale. Results: There were no significant differences between robotic gastrectomy (RG) and laparoscopic gastrectomy (LG) regarding conversion rate, reoperation rate, mortality, overall complications, anastomotic leakage, distal and proximal resection margin distances, and recurrence rate. However, mean blood loss (mean difference - MD - -19.43 mL, p<0.00001), length of stay (MD -0.50 days, p=0.0007), time to first flatus (MD -0.52 days, p<0.00001), time to oral intake (MD -0.17 days, p=0.0001), surgical complications with a Clavien-Dindo grade ≥ III (relative risk - RR - 0.68, p<0.0001), and pancreatic complications (RR 0.51, p=0.007) were significatively lower in the RG group. Furthermore, the number of retrieved lymph nodes was significantly higher in the RG group. Nevertheless, the RG group showed a significantly higher operation time (MD 41.19 min, p<0.00001) and cost (MD 3684.27 US Dollars, p<0.00001). Conclusion: This meta-analysis supports the choice of robotic surgery over laparoscopy concerning relevant surgical complications. However, longer operation time and higher cost remain crucial limitations. Randomized clinical trials are required to clarify the advantages and disadvantages of RG.